Assessing sustainability from the corporate perspective - Rorarius, Jonas (2008)
Today, there is an increasing awareness of problems related to aspects of sustainability in the world. These problems are addressed in various forms, from an economic, environmental and socio-cultural perspective. From a corporate point of view it would be ideal if all of these perspectives were included in assessment that serves as grounds for policies, plans and programs. The existing assessment tools are argued to be inappropriate as they do not cover all of the aspects of sustainability. Thus, there is a need for better sustainability assessment tools to help corporate ex-ante decision-making.